Salmosan, a β-Galactomannan-Rich Product, Protects Epithelial Barrier Function in Caco-2 Cells Infected by Salmonella enterica Serovar Enteritidis. Issue 8 (29th June 2016) - Brufau, M Teresa; Campo-Sabariz, Joan; Bou, Ricard; Carné, Sergi; Brufau, Joaquim; Vilà, Borja; Marqués, Ana M; Guardiola, Francesc; Ferrer, Ruth; Martín-Venegas, Raquel
Abstract: Background: One promising strategy for reducing human salmonellosis induced by Salmonella Enteritidis is to supplement animal diets with natural feed additives such as mannan oligosaccharides (MOSs). Objective: We sought to investigate the potential role of Salmosan (S-βGM), an MOS product extremely rich in β-galactomannan, in preventing epithelial barrier function disruption induced by S. Enteritidis colonization in an in vitro model of intestinal Caco-2 cells in culture. Methods: Differentiated Caco-2 cells were incubated for 3 h with S. Enteritidis at a multiplicity of infection of 10 in the absence or presence of 500 μg S-βGM/mL. Paracellular permeability (PP) was assessed by transepithelial electrical resistance (TER), D-mannitol, and fluorescein isothiocyanate-dextran (FD-4) flux. Tight junction proteins and cytoskeletal actin were also localized by confocal microscopy. Reactive oxygen species (ROS) and lipid peroxidation products were evaluated. Scanning and transmission electron microscopy were used to visualize S. Enteritidis adhesion to, and invasion of, the Caco-2 cell cultures. Results: Compared with controls, TER was significantly reduced by 30%, and D-mannitol and FD-4 flux were significantly increased by 374% and 54% in S. Enteritidis-infected cultures, respectively. The presence of S-βGM in infected cultures induced total recoveries of TER and FD-4 flux to values that did not differ from the control and a partial recovery of D-mannitol flux. These effects were confirmed by immunolocalization of actin, zonula occludens protein 1, and occludin. Similar results were obtained for Salmonella Dublin. The protection of S-βGM on PP in infected cultures may be associated with a total recovery of ROS production to values that did not differ from the control. Moreover, S-βGM has the capacity to agglutinate bacteria, leading to a significant reduction of 32% in intracellular S . Enteritidis. Conclusion: The results demonstrate that S-βGM contributes to protecting epithelial barrier function in a Caco-2 cell model disrupted by S. Enteritidis.